How Much Do Agricultural Policies Restrict Trade? Comparing Trade Restrictiveness Indexes - Anderson, Kym (World Bank, Washington, DC, 2012)
Recently the Bank has provided new indicators for monitoring the extent to which agricultural policies restrict international trade in farm goods. They come from two studies with differing methodologies and data sources, and each provides less-than-perfect estimates. This note shows how and explains why the two indexes differ for some countries.